2017
DOI: 10.1080/23328940.2017.1368877
|View full text |Cite
|
Sign up to set email alerts
|

Performance in complex motor tasks deteriorates in hyperthermic humans

Abstract: Heat stress, leading to elevations in whole-body temperature, has a marked impact on both physical performance and cognition in ecological settings. Lab experiments confirm this for physically demanding activities, whereas observations are inconsistent for tasks involving cognitive processing of information or decision-making prior to responding. We hypothesized that divergences could relate to task complexity and developed a protocol consisting of 1) simple motor task [TARGET_pinch], 2) complex motor task [Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 46 publications
4
72
0
Order By: Relevance
“…Piil and colleagues recently showed that the negative impact of hyperthermia was exposed only when task complexity was maximised (Piil et al . ). Although the pro/anti‐point task (which combines all of the tasks, i.e.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Piil and colleagues recently showed that the negative impact of hyperthermia was exposed only when task complexity was maximised (Piil et al . ). Although the pro/anti‐point task (which combines all of the tasks, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…; Piil et al . ). The link between CBF and CDO 2 to cognitive functioning is complex in these environments.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations